Hematological effects of Ipomoea batatas (camote) and Phyllanthus niruri (sampa-sampalukan) from Philippines in the ICR mice (Mus musculus) - Montejo, Jessa Fidel (Animo Repository, 2015)
Objective: To analyze the hematological effects of administering Ipomoea batatas (I. batatas) and Phyllanthus niruri (P. niruri) in the ICR mice. Methods: Powdered leaves of I. batatas and P. niruri were fed to mice for 4 weeks. A total of six groups were used to determine the effect of the plants to the complete blood count of the mouse. Group A (blank control) mice were feed with pellets only; Group B (negative control) mice were fed with pellets coated with honey; Group C (low dosage) mice were fed with honey-coated pellets and powdered leaves of I. batatas at 10 g/kg body weight of the mouse; Group D (high dosage) mice were fed with honey-coated pellets and powdered leaves of I. batatas at 20 g/kg body weight of the mouse; Group E (low dosage) mice were fed with honey-coated pellets and powdered leaves of P. niruri at 10 g/kg body weight of the mouse; and Group F (high dosage) mice were fed with honey-coated pellets and powdered leaves of P. niruri at 20 g/kg body weight of the mouse. Complete blood count was performed on Days 0, 14 and 28. Results: It was shown that I. batatas can increase the values of hematocrit and hemoglobin on both the low dose and high dose at Day 28 and red blood cells (RBC) on both Days 14 and 28 of testing. On the other hand, P. niruri can increase RBC, hematocrit and hemoglobin on Day 28 with only the low dose. There were no significant differences with white blood cell, absolute granulocyte, lymphocyte and monocyte, and platelet counts observed for both plant samples. Conclusions: I. batatas and P. niruri have effects on the hematocrit, RBC and hemoglobin levels in mice. © 2015 by the Asian Pacific Journal of Tropical Biomedicine.